Perilaku Struktur terhadap Beban Impak - Nurhuda, Ilham (Department of Civil Engineering, Diponegoro University, 2008)
This paper is concerned with the prediction of impact load from a hard body object and response of the target structure. Two approaches in predicting the magnitude and duration of impact loading, namely half-space approach and interaction approach, were studied in this paper. This study showed that load and structure response from both approaches were very different. Since the interaction approach considered the effect of structure flexibility on the load and response history, this approach showed more realistic results than the half-space approach.Keyword: impact, dynamic, plate, time historyPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3667[How to cite: Nurhuda, I. (2008), Perilaku Struktur terhadap Beban Impak, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, No. 1, pp. 79-86]